2022
DOI: 10.3389/fonc.2022.907472
|View full text |Cite
|
Sign up to set email alerts
|

Long Intergenic Noncoding RNA00265 Enhances Cell Viability and Metastasis via Targeting miR-485-5p/USP22 Axis in Osteosarcoma

Abstract: Osteosarcoma is one of the bone malignancies in children and adolescents. Long noncoding RNAs (lncRNAs) have been demonstrated to participate in osteosarcoma development and progression. Linc00265 has been shown to involve in osteosarcoma oncogenesis; however, the underlying mechanism is largely unclear. In this study, we investigated the function of linc00265 in osteosarcoma cells, including cell viability, migration and invasion. Moreover, we elucidated mechanistically the involvement of linc00265 in osteosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…MALAT1: FW: GGA TCC TAG ACC AGC ATG CC; RV: AAA GGT TAC CAT AAG TAA GTT CCA GAA AA ( 31 ). The detailed method for PCR was described previously ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…MALAT1: FW: GGA TCC TAG ACC AGC ATG CC; RV: AAA GGT TAC CAT AAG TAA GTT CCA GAA AA ( 31 ). The detailed method for PCR was described previously ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides these gene mutations, non-coding RNAs have been reported to involve in regulating TME and immunotherapy in lung cancer. Non-coding RNAs have been reported to involved in human cancer development and progression ( Ghafouri-Fard et al, 2020 ; Yan and Bu, 2021 ; Chen T. et al, 2022 ; Liu and Shang, 2022 ). Evidence has shown that lncRNAs play an essential role in NSCLC initiation, development and progression ( Osielska and Jagodzinski, 2018 ; Wang et al, 2018 ; Hu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that microRNA (miRNA) has approximately 22 nucleotides and targets gene expression via regulation of post-transcription (19,20). Now, noncoding RNAs have been validated to critically participate in oncogenesis in various types of cancers (21)(22)(23)(24)(25). Not surprisingly, noncoding RNAs regulated numerous cellular biological processes and dysregulated noncoding RNAs lead to various diseases, including cancer (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%